Optimization of Medium Composition and Fluidized Bed Drying Conditions for Efficient Production of Dry Yeast - Hyun-Jin Kang; Hwan Hee Yu; Chang-Won Cho; Young Kyung Rhee; Tae-Wan Kim; Young-Wook Chin (Microorganisms)
Yeast formulations such as dry yeast are essential for supplying microbial starters to the alcoholic beverage industry. In Korea, the expensive freeze-drying method is used to manufacture brewer’s dry yeast, and therefore an economical process such as fluidized bed drying is needed. In the dry yeast manufacturing process, the medium and drying conditions are key factors that determine its quality and manufacturing cost. In this study, we aimed to optimize the medium composition and fluidized bed drying conditions for the efficient production of dry yeast. Muscovado and corn steep liquor were used as the carbon and nitrogen sources, respectively, and their optimal concentrations were identified using response surface methodology for efficient cultivation of Saccharomyces cerevisiae ReY4-7 isolated from nuruk. Central composite design analysis revealed that the optimal medium composition was 146.12 g/L muscovado and 58.68 g/L corn steep liquor. A dry cell weight of 36 g/L was achieved during 24 h of batch fermentation in a 30-L bioreactor containing this medium. Analysis of protective agents against fluidized bed drying revealed Span 80 as the strongest protective agent for S. cerevisiae ReY4-7. Response surface methodology revealed 50 °C and 41.45 min as the optimal fluidized bed drying conditions, under which the viable cell count reached 10.28 log CFU/g, comparable to that of the commercial dry yeast products. Overall, optimization of the medium and drying conditions significantly improved the final cell concentration in the cultivation process and the viable cell count in the drying process of dry yeast.